Optimality of intuitionistic fuzzy fractional transportation problem of type-2. Issue 1 (2nd January 2019) - Anukokila, P.; Anju, A.; Radhakrishnan, B.
Abstract: In this paper, we formulate an effective method to find an optimal solution of trapezoidal intuitionistic fuzzy fractional transportation problem[TIFFTP] of type-2. The proposed method achieve its goal successively when compared to the existing methods (Gupta and Anupum). Trapezoidal ranking method is used, which is based on the area of both membership and non membership parts of the numbers. An illustrative example is provided to demonstrate the feasibility of this method.